Analysis and Design of Shear Wall Coupling Beam Using Hybrid Steel Truss Encased in Reinforced Mortar. (2017) - Chairunnisa, Nursiah; Satyarno, Iman; Muslikh,; Aminullah, Akhmad
Abstract: Shear wall coupling beam using hybrid steel truss encased in reinforced mortar is proposed in this paper as an alternative method of that conventional reinforced concrete coupling beam. The application of steel truss is to substitute the need of longitudinal, transversal, and diagonal steel reinforcement in the reinforced concrete shear wall coupling beam which is commonly very difficult to install on site due to the crowded of steel bars reinforcement. Meanwhile, the application of encased reinforced mortar is mainly to prevent the steel truss from premature buckling and at the same time may also to increase the shear and flexural capacity. Only analytical and design examples of various arrangement of steel truss and encased mortar are given in this paper as the laboratory tests are still under the way. The examples use typical reinforced concrete coupling beam with span to depth ratio that requires conventional diagonal reinforcement. Various design using steel truss coupling beam with and without buckling consideration, steel truss coupling beam encased in mortar only, and steel truss coupling beam encased in reinforced mortar as alternative design are discussed. It is found that the alternative method gives the most reliable alternative.